2014
DOI: 10.1007/s00415-014-7519-0
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of horizontal canal benign paroxysmal positional vertigo is truly short

Abstract: The objective of the study is to characterize the natural course of positional vertigo and nystagmus in patients with horizontal canal benign paroxysmal positional vertigo (h-BPPV) and to analyze the difference in the natural course between the two variants of h-BPPV. We conducted a prospective study in 106 patients with geotropic type h-BPPV [h-BPPV (Geo)] (n = 43) and apogeotropic type h-BPPV [h-BPPV (Apo)] (n = 63) who agreed and signed the written informed consent of no treatment. All patients were asked t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…Second, the natural resolution of BPPV is more common in LC-BPPV especially the geotropic variant (2,6,25). A study showed that the course from the onset to remission of vertigo in 36 patients with untreated geotropic LC-BPPV was 16 T 19 days, and 53% of them had spontaneous disappearance of vertigo within 7 days (6), and a recent study indicated that the course was shorter (6.7 T 6.3 d) in the patients with untreated geotropic LC-BPPV (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the natural resolution of BPPV is more common in LC-BPPV especially the geotropic variant (2,6,25). A study showed that the course from the onset to remission of vertigo in 36 patients with untreated geotropic LC-BPPV was 16 T 19 days, and 53% of them had spontaneous disappearance of vertigo within 7 days (6), and a recent study indicated that the course was shorter (6.7 T 6.3 d) in the patients with untreated geotropic LC-BPPV (25).…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that the course from the onset to remission of vertigo in 36 patients with untreated geotropic LC-BPPV was 16 T 19 days, and 53% of them had spontaneous disappearance of vertigo within 7 days (6), and a recent study indicated that the course was shorter (6.7 T 6.3 d) in the patients with untreated geotropic LC-BPPV (25). But a previous study demonstrated that only 17% of 18 patients with untreated LC-BPPV showed spontaneous resolution of vertigo after 1 week, and 28% of the patients had persistent vertigo for several months (20).…”
Section: Discussionmentioning
confidence: 99%
“…BPPV is often a self-limiting condition, 12,13 but can be persistent or recurrent. [14][15][16][17] BPPV may cause considerable handicap for patients, restricting work as well as other activities of daily living.…”
Section: Introductionmentioning
confidence: 99%
“…In general, this subtype of BPPV has a favorable prognosis. A prospective study evaluating its natural history found that spontaneous resolution occurred by 6.7 and 3.7 days for the geotropic and apogeotropic variants, respectively (8).…”
Section: Discussionmentioning
confidence: 99%